Qualitative Study of Community Participation Behavior in the Family Planning Program at the Kajuara Community Health Center, Bone District, South Sulawesi, Indonesia - Mustika Eka Pratama Musakkar; Erniati Erniati; Arlin Adam; Andi Alim (Journal of Health Promotion and Behavior, 2023)
Background: The high birth rate is the main reason for the need for family planning services. Many women experience difficulties in determining the choice of type of contraception. This is not only because of the limited available methods but also because of their ignorance to make the right choice according to age, number of children and the side effects that often arise. This study aimed to obtain in-depth information about the behavior of community participation in the family planning program at the Kajuara Community Health Center, Bone Regency. Subjects and Method: The type of research used is descriptive qualitative research. The number of informants in this study was 7 people. The variables of this study are people's behavior, knowledge, attitudes, and actions. These research variables in a qualitative approach are referred to as the research focus. Data collection was done through in-depth interviews. Data analysis using "content analysis". While the technique of testing the validity of the data using data triangulation. Results: The results showed that basically, the community at the Kajuara Community Health Center knew about the Family Planning program, its benefits, and objectives, but the information obtained about the Family Planning program was not fully obtained. The attitude of the people who are less responsive to participation in the Family Planning program does not mean they are afraid of not having children but are afraid of the effects of these contraceptives. The actions of people who do not participate in the Family Planning program are due to information from other people regarding the effects of contraceptives which makes people not want to participate in the Family Planning program. Conclusion: This study concludes that there is a need to increase public knowledge about the Family Planning program through intensive counselling in the community by health workers. It is recommended that the community at the Kajuara Community Health Center support the Family Planning program that has been programmed by the government by participating in the program. It is hoped that mothers will not be influenced by information from other people about the effects of family planning and seek information about family planning programs from health workers. Keywords: participation behavior, family planning program, knowledge, attitudes, actions. Correspondence: Erniati. Faculty of Public Health, University of Pejuang Republic Indonesian. Jl. Raya Baruga, Antang, Manggala, Makassar, 90234 South Sulawesi, Indonesia. Email: erniatibnn@gmail.com. Mobile: +62 852-5684-0988.